Mechanical Behavior of the Extraction Mud Dam for Use in the Manufacture of CEB - Cherif, Benaicha Amar; Ali, Fourar; Tarek, Mansouri; Massouh, Fawaz (Civil Engineering Journal, 2021)
The aim of this work is to study the mechanical behavior of the sediments extracted from the Koudiet Meddaouar, Timgad dam (Algeria), for a possible valorization in the field for building works in order to minimize this phenomenon which is currently a concern for the operators and the persons in charge of the mobilization of the water resources. This siltation therefore severely limits its storage capacity and consequently itâ€™s operating life. The extraction of the sediments accumulated in the dam's reservoir is therefore imperative, on the pain of seeing it perish in the medium term. These sediments are, however, of great geotechnical and mechanical value. The results of the tests conducted in the laboratory have enabled us to identify the different sediments from a physical and geotechnical point of view In front of the difficulties noted in the control of the silting up of the dams in Algeria, a very important quantity of silt being deposited annually in the dams. In order to achieve our objective, different mixtures of silt with or without lime treatment, cement glass fibers and powdered fibers were studied for the possible manufacture of Compressed Earth Bricks (CEB). The results obtained show that some of the mixtures present very interesting results in the different tests (compression and bending), verifying the conditions of the standards in force and thus allowing their use in the field of the manufacture of building materials.Â Doi: 10.28991/cej-2021-03091759 Full Text: PDF